Massic properties of the TE-modes in a lossless waveguide - Erden, Fatih; Çoşan, Ahmet Arda; Tretyakov, Oleg A. (Institute of Electrical and Electronics Engineers Inc., 2018)
Analytical solutions of the TE-modal fields for a lossless waveguide are expressed within the framework of the evolutionary approach to electrodynamics (EAE). Electric and magnetic field vectors, which have physical dimensions of volt per meter and amper per meter respectively, are factorized in SI units. Elements of the modal basis that depend on transverse coordinates, r, and the modal amplitudes that depend on longitudinal coordinate, z, and time, t, are obtained via solving the boundary-eigenvalue problem. Exact solutions for mass and momentum are derived and presented graphically. © 2018 Elsevier B.V., All rights reserved.
Kayipsiz Dalga Kilavuzunda TE- Modlarinin Kütlesel Özellikleri
26th IEEE Signal Processing and Communications Applications Conference, SIU 2018 -- Izmir; Altin Yunus Resort ve Thermal Hotel -- 137780
Keywords: Electromagnetics; Energy; Klein-Gordon equation; Mass; Maxwell's equations; Momentum; Time-domain; Waveguide